Makam Gus Dur, Ikon Pariwisata Jombang* - Lexi Pranata; Dewa Gde Satrya (UNUSA Press, 2019)
Tebuireng Islamic Boarding School, Jombang district, which is integrated with the tombs of the founders of the Nahdlatul Ulama (NU) and national heroes, is increasingly visited by pilgrims since KH. Abdurrahman Wahid (Gus Dur) died and was buried there. The arrival of the pilgrims was in addition to a form of homage to the scholars of the founders of Nadhlatul Ulama (NU), also to pray. This motivation is typical in pilgrimage tours. Gus Dur’s grave deserves to be designated as an icon of Jombang district tourism. As a pilgrimage tourist destination, the iconic tomb complex with Gus Dur’s Tomb has several advantages to be designated as Jombang tourism icons which are then expected to provide added value for Jombang district. This article is conceptual paper, giving a review of Gus Dur’s grave designation as an icon of Jombang tourism. The research approach is qualitatively descriptive, where primary data sources are obtained from data collection through interviews and supported by the observation process. Secondary data sources are carried out through the study of related literature. The formulation of the problem in this study is how the chances of Gus Dur’s grave becoming an icon of Jombang tourism? The conclusion of this study is that the tomb of Gus Dur is appropriate to be used as an icon of Jombang tourism, with consideration, first, the tomb of Gus Dur have an advantage as a heritage area that has high historical value, and is strategically significant for the progress of Jombang tourism in particular. Second, the geographical location of Gus Dur’s tomb which became one area with Tebuireng Islamic Boarding School, also higher education, and the National Islamic Museum K.H. Hasyim Asy’ari in one area will focus the relevant government agencies to carry out development programs as a follow-up to iconic tourism designation. Third, the Tomb of Gus Dur is important area in the establishment of NU, which is expected to have a positive impact on the surrounding area when arranged in such a way. Fourth, in terms of tourism components, Gus Dur’s Grave has complete appeal, good accessibility, existing facilities but needs to be developed.